Pharmaceutical packaging having a coating comprising polycyanurate
By applying a low friction coating of cyanurate on glass drug packaging, the problem of glass being susceptible to mechanical damage is solved, and the effect of improving the mechanical durability and thermal stability of glass is achieved.
Patent Information
- Application Number
- CN202080070777.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-09
- Filing Date
- 2020-08-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2040-08-03
AI Technical Summary
Existing glass drug packaging parts are susceptible to mechanical damage during manufacturing, transportation and treatment, resulting in reduced strength and increased cracks, affecting the sterility of the drug and the integrity of the packaging.
Using a low friction coating containing cyanurate, a coating that is heat-stabilized at high temperatures is formed by depositing the coating precursor mixture onto the surface of the glass container and heating it to improve the mechanical durability of the glass.
The friction coefficient of glass drug packaging is reduced, its resistance to mechanical damage is enhanced, and the mechanical properties after high temperature treatment is improved, ensuring the sterility of the drug and the integrity of the packaging.
Smart Images

Figure CN115175857B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority under 35 U.S.C. §120 to U.S. Provisional Application Serial No. 62 / 884,731, filed on August 9, 2019, the contents of which are hereby relied upon and incorporated herein by reference in their entirety.
[0003] background Technical Field
[0004] The present description relates generally to glass articles and, more particularly, to coatings on glass articles, such as pharmaceutical packaging. Background Art
[0005] Historically, glass has been used as a preferred material for packaging pharmaceuticals due to its airtightness, optical clarity, and excellent chemical durability relative to other materials. Specifically, glass used for pharmaceutical packaging requires sufficient chemical durability without affecting the stability of the pharmaceutical composition contained therein. Glass with suitable chemical durability for many pharmaceutical applications includes those glass compositions in the ASTM standard "Type 1B", whose chemical durability has been historically proven.
[0006] However, the use of glass for these applications is limited by the mechanical properties of glass. In the pharmaceutical industry, glass breakage is a safety concern for end users because the broken package and / or the contents of the package may injure the end user. Glass breakage on the filling line also results in expensive drug losses and may even lead to recalls due to defective packages or broken glass contained in adjacent sealed packages on the filling line. In addition, non-catastrophic breakage (i.e., when the glass cracks but does not break) may cause the contents to lose their sterility, which in turn may lead to expensive product recalls.
[0007] Specifically, the high processing speeds used in the manufacture and filling of glass pharmaceutical packages can result in mechanical damage (e.g., abrasion) on the surface of the package when the package comes into contact with processing equipment, handling equipment, and / or other packaging. This mechanical damage can significantly reduce the strength of glass pharmaceutical packages, leading to an increased likelihood of cracks in the glass, which can compromise the sterility of the drug contained in the package or cause the package to fail entirely.
[0008] One method of improving the mechanical durability of glass packaging is to heat temper and / or chemical temper the glass packaging. Heat tempering strengthens glass by inducing surface compressive stress during rapid cooling after forming. For glass products (such as windows) with flat geometry, glass products with a thickness greater than about 2mm and glass compositions with high thermal expansion, this technology is very effective. However, pharmaceutical glass packaging usually has complex geometry (vials, tubular, ampoules, etc.), thin walls (sometimes between about 1-1.5mm), and is made of low expansion glass, which makes glass pharmaceutical packaging unsuitable for strengthening by conventional heat tempering. Chemical tempering also strengthens glass by introducing surface compressive stress. Stress is introduced by immersing the product in a molten salt bath. Because the ions from the glass are replaced by larger ions from the molten salt, compressive stress is induced in the surface of the glass. The advantage of chemical tempering is that it can be used on complex geometry, thin samples, and is relatively less sensitive to the thermal expansion properties of the glass substrate.
[0009] However, while the above-mentioned tempering techniques improve the ability of strengthened glass to withstand blunt impacts, these techniques are less effective in improving the glass's resistance to abrasion (such as scratches) that may occur during manufacturing, transportation and handling. These defects may make the glass more susceptible to breakage.
[0010] Therefore, there is a need for alternative glass articles having improved resistance to mechanical damage. Summary of the invention
[0011] In one or more embodiments of the present disclosure, a drug package may include a glass container, the glass container including a first surface and a second surface opposite to the first surface. The first surface may be an outer surface of the glass container. The drug package may also include a coating, the coating being located above at least a portion of the first surface of the glass container. The coating may include polycyanurate.
[0012] In one or more additional embodiments of the present disclosure, a pharmaceutical package may include a glass container comprising a first surface and a second surface opposite the first surface. The first surface may be an outer surface of the glass container. The pharmaceutical package may also include a coating located above at least a portion of the first surface of the glass container. The coating may include a polymer formed from at least one or more cyanate ester monomers.
[0013] In one or more additional embodiments of the present disclosure, a coated pharmaceutical package can be produced by a method comprising depositing a precoating mixture onto a first surface of an outer surface of a glass container, and heating the precoating mixture to form a coating on the outer surface of the glass container. The precoating mixture can include one or more cyanate esters, and the coating can include a polycyanurate.
[0014] Additional features and advantages of coatings that can be used to coat glass articles, coated glass articles, and methods and processes for making the coated glass articles are listed in the following detailed description, some of which will be readily apparent to those skilled in the art from the description or recognized by practicing the embodiments described herein, including the following detailed description, claims, and drawings.
[0015] It should be understood that both the foregoing general description and the following detailed description describe various embodiments and are intended to provide an overall review or framework for understanding the nature and characteristics of the claimed subject matter. The included drawings provide a further understanding of the various embodiments, and the drawings are incorporated into and constitute a part of this specification. The drawings illustrate the various embodiments described herein and, together with the description, are used to explain the principles and operations of the claimed subject matter. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 According to one or more embodiments shown and described herein, a cross-sectional view of a glass container having a low friction coating is schematically depicted;
[0017] Figure 2 According to one or more embodiments shown and described herein, a schematic diagram of a Figure 1 An enlarged cross-sectional view of a glass container;
[0018] Figure 3 According to one or more embodiments shown and described herein, a test bench for determining a coefficient of friction between two surfaces is schematically depicted; and
[0019] Figure 4 According to one or more embodiments shown and described herein, percent transmission data for the samples of Example 2 is plotted versus wavelength of light. DETAILED DESCRIPTION
[0020] Reference will now be made in detail to various embodiments of coatings, glass articles with coatings, and methods for producing the same, examples of which are schematically illustrated in the accompanying drawings. Such coated glass articles may be glass containers suitable for various packaging applications, including but not limited to as pharmaceutical packaging. It should be understood that coated glass articles may refer to coated pharmaceutical packaging as described in the present disclosure. In one or more embodiments, coatings and / or coated pharmaceutical packaging are thermally stable when exposed to high temperatures (e.g., high temperatures used during the depyrogenation process) after initial coating application and curing. For example, the coated glass articles described herein may fully retain their low coefficient of friction after heat treatment, and / or the color may not substantially turn yellow after such heat treatment. These pharmaceutical packagings may or may not contain pharmaceutical compositions. In one or more embodiments, the coating may include one or more polycyanurates. In some embodiments, the entire coating may be a polycyanurate. In one or more embodiments, the coating may be a low friction coating, for example, those having a coefficient of friction less than that of bare glass (e.g., less than 0.7). In one or more embodiments of the present disclosure, a coating comprising polycyanurate may have desirable functionality and / or properties compared to other polymeric materials that may be used for coatings on pharmaceutical packaging. For example, a coating comprising or consisting of polycyanurate may be provided to reduce the coefficient of friction, improve adhesion without the use of silane coupling agents, and / or improve solubility in non-toxic solvents during application compared to coatings made from other types of polymers.
[0021] Various embodiments of coatings, glass articles having coatings, and methods of forming the same will be described in more detail herein with particular reference to the accompanying drawings. Although the embodiments of the coatings described herein are applied to the outer surface of a glass container, it should be understood that the coatings can be used as coatings on a variety of materials, including non-glass materials, and on substrates other than containers, including but not limited to glass display panels, etc.
[0022] In general, the coating can be applied to the surface of a glass article, which can be used, for example, as a container for a pharmaceutical package. The coating can provide advantageous properties to the coated glass article, such as a reduced coefficient of friction and improved damage resistance. The reduced coefficient of friction can impart improved strength and durability to the glass article by alleviating friction damage to the glass. In addition, after exposure to high temperatures and other conditions, such as conditions experienced during packaging and pre-packaging steps for packaging drugs, such as after pyrogen removal, freeze drying, autoclaving, etc., the coating can maintain the above-mentioned improved strength and durability characteristics. Therefore, under some conditions, such as under the conditions used in pyrogen removal, the coating and the glass article having the coating can be thermally stable.
[0023] Figure 1 A coated glass article, specifically a cross-sectional view of a coated glass container 100, is schematically depicted. The coated glass container 100 includes a glass body 102 and a coating 120. The glass body 102 has a glass container wall 104 extending between an outer surface 108 (i.e., a first surface) and an inner surface 110 (i.e., a second surface). The inner surface 110 of the glass container wall 104 defines an interior volume 106 of the coated glass container 100. The coating 120 is located on at least a portion of the outer surface 108 of the glass body 102. As used herein, a coating can be "located on a substrate" without being in direct contact with the substrate, such as if there is an intervening layer between the substrate and the coating located above the substrate. In some embodiments, the coating 120 can be located on substantially the entire outer surface 108 of the glass body 102. In some embodiments, for example Figure 1 As depicted, coating 120 may be in direct contact with (ie, bonded to) glass body 102 at exterior surface 108. Coating 120 has exterior surface 122 and a surface 124 that contacts glass body 102 at the interface of coating 120.
[0024] In one or more embodiments, the coated glass container 100 is a pharmaceutical packaging. For example, the glass body 102 can be in the following shapes: a vial, an ampoule, an ampoule bottle, a bottle, a flask, a tubular bottle, a beaker, a barrel, a glass bottle, a cylinder, a syringe body, etc. The coated glass container 100 can be used to hold any composition, and in one embodiment, can be used to hold a pharmaceutical composition. The pharmaceutical composition can contain any chemical substance intended for medical diagnosis, cure, treatment or prevention of a disease. Examples of pharmaceutical compositions include, but are not limited to, drugs, medicines, medicaments, pharmaceutical agents, medical agents, etc. The pharmaceutical composition can be in the form of a liquid, a solid, a gel, a suspension, a powder, etc.
[0025] Reference now Figure 1 and 2In one embodiment, coating 120 comprises a single layered structure, which is sometimes referred to herein as a "single layer" structure. For example, coating 120 may have a substantially uniform composition containing only polycyanurate, or polycyanurate mixed with one or more additional components. If two or more components are included in coating 120, coating 120 may be mixed but not completely uniform. For example, in one or more embodiments, one or more chemical components of the mixture may be concentrated at the interface of coating 120 (e.g., the interface with glass body 102 or outer surface 122). In such an embodiment, the local concentration of the chemical components may vary in different areas of coating 120. However, it should be understood that the term "mixed" as used herein refers to a layer having at least some dispersion of at least two chemical components, and includes layers that are not completely uniform. In general, the mixed layer is deposited as a mixture of two or more chemical components contained in the coating precursor mixture.
[0026] As described herein, coating 120 includes one or more polycyanurates. In general, polycyanurates are thermally stable polymers that do not significantly degrade or do not degrade at all when exposed to a temperature suitable for removing pyrogens, such as at least about 250°C, at least about 260°C, at least about 280°C, or even at least about 300°C for about 30 minutes. Polycyanurates as described herein include polymers formed from cyanate monomers. In other embodiments, polycyanurates can be formed from prepolymers containing cyanate monomers. Prepolymers refer to partially polymerized substances that are further polymerized to form polycyanurates in coating 120. As proposed herein, polycyanurates also include polymers having a polycyanurate backbone modified by other chemical components, or copolymers including one or more cyanate monomer units and other non-cyanate monomers. For example, the polycyanurate can be a homopolymer formed from a single cyanate species as a monomer unit, a copolymer (random or block copolymer) formed from two or more cyanate species, or a copolymer comprising some polycyanurate backbone structures and other monomer species, as described herein. The polycyanurate can be formed by polymerization, for example, by curing by heating or other methods, which utilize monomers or prepolymers or a combination thereof.
[0027] The coating 120 may contain at least 10 wt%, at least 20 wt%, at least 30 wt%, at least 40 wt%, at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt%, at least 98 wt%, at least 99 wt%, or even at least 99.9 wt% of the polycyanurate. The polycyanurate in the coating 120 may contain at least 10 wt%, at least 20 wt%, at least 30 wt%, at least 40 wt%, at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt%, at least 98 wt%, at least 99 wt%, or even at least 99.9 wt% of a component derived from a cyanate ester. The portion of the coating derived from any one cyanate ester may comprise at least 10 wt %, at least 20 wt %, at least 30 wt %, at least 40 wt %, at least 50 wt %, at least 60 wt %, at least 70 wt %, at least 80 wt %, at least 90 wt %, at least 95 wt %, at least 98 wt %, at least 99 wt %, or even at least 99.9 wt %, based on the total weight of the polycyanurate.
[0028] In an embodiment of the present disclosure, the polycyanurate may include a three-dimensional cross-linked structure in which the -OCN functional groups of the cyanate monomers form a triazine ring. The polycyanurate may include a monomer unit formed from one or more cyanates. The general chemical structure of the cyanate that can be used to form the polycyanurate is shown in Chemical Structure 1. As shown, the cyanate includes -OCN functional groups (e.g., two -OCN functional groups connected by an R group).
[0029] Chemical structure 1:
[0030]
[0031] In the embodiments of the present disclosure, there is no necessary restriction on the R group. However, in some embodiments, the cyanate ester used may include a bisphenol functional group, which is referred to as a bisphenol cyanate ester herein. In general, bisphenol refers to a compound including two phenol groups, each of which includes an oxygen atom directly connected to the phenol group. This bisphenol functional group can provide good heat resistance. Tables 1 and 2 provide examples of bisphenol cyanates that may be included in polycyanurate. For example, the cyanate ester used to form polycyanurate can be selected from bisphenol A cyanate, bisphenol E cyanate, C, C'-((2,2,2-trifluoro-1-(trifluoromethyl)ethylidene)di-4,1-phenylene) ester (sometimes also referred to as hexafluorobisphenol A cyanate), tetramethyl bisphenol F cyanate, bisphenol M cyanate, C, C'-((2,2,2-trifluoro-1-(trifluoromethyl)ethylidene)di-4,1-phenylene) ester, or a combination thereof. But it should be understood that other cyanates can be used, therefore, Tables 1 and 2 are only examples of possible cyanates.Cyanates can include heteroatoms, such as but not limited to Si, P and / or F.In addition, it is contemplated that aromatic dicyanates with phenylphosphine oxide, sulfone and carbonyl can be used, which can have excellent reactivity and thermal properties.In addition, cyanates, for example, include those of phenolic resin varnish or polystyrene, and are also contemplated for use in embodiments herein.It should be understood that the prepolymer that can be used to form polycyanurate can include these cyanates as monomer units.
[0032] Table 1:
[0033]
[0034]
[0035] Table 2:
[0036]
[0037] According to another embodiment, polycyanurate can be formed by one or more of the cyanate esters disclosed in chemical structures 2-56 herein. The cyanate esters disclosed in chemical structures 2-56 may include, but are not limited to, tris(cyanophenoxy)phosphazene, poly(phenyl)phenylene-dicyanate, polyaryletherketone (PEK)-dicyanate, polyethersulfone (PES)-dicyanate, poly(cyanophenylmaleimide), poly(4-cyanophenylstyrene), poly(4-cyanophenylstyrene)-co-MMA, poly(4-cyanophenylstyrene)-co-BD, bis(3-allyl-4-cyanophenyl)propane, bis(3-propenyl-4-cyanophenyl)propane, 4-cyanophenyl, 4-cyanobenzoate, and 4,4'-dicyanobiphenyl. It should be understood that polycyanurate can be formed by one cyanate component, or by a variety of cyanate components, such as those in chemical structures 2-56.
[0038]
[0039]
[0040]
[0041]
[0042]
[0043]
[0044]
[0045]
[0046]
[0047] In one or more embodiments, cyanate esters can be synthesized from phenols and cyanogen halides in the presence of tertiary amines at low temperatures. Chemical Reaction Scheme A below represents one embodiment of this reaction.
[0048]
[0049]
[0050] According to the embodiments described herein, polycyanurate can be formed by curing cyanate (e.g., by heating). The heating required for curing can be relatively mild, for example, below 230°C. The following chemical reaction scheme B depicts a general curing reaction for forming polycyanurate from cyanate. During the curing process, a triazine ring is formed by the cyclotrimerization of three cyanate groups (-OCN) to obtain a highly cross-linked polycyanurate polymerization network. The reaction generally does not produce any by-products. In addition, the reaction does not release toxic compounds, such as HCN, which may be harmful to the environment and / or people who come into contact with these substances. Therefore, the cyclotrimerization of cyanate as shown in chemical reaction scheme B can be classified as green chemistry and click chemistry. For example, the curing does not form water, such as water produced in some other polymerization reactions. In other embodiments, this curing may be less corrosive to processing equipment and / or may exhibit less shrinkage after curing.
[0051]
[0052] In other embodiments, polycyanurates can be functionalized by other reagents, or can be polymers formed by mixtures of cyanate esters and other polymers. For example, cyanate esters can react with many other groups or reagents, such as water, phenols, epoxides, etc. For example, co-curing of cyanate esters and epoxides can be used to form polycyanurates. The co-reaction of cyanate esters and epoxides can yield a product whose water resistance and dielectric properties are improved compared to homopolymers formed by cyanate esters and epoxides. Such co-cured polycyanurates are described in "J. Bauer & M. Bauer (1990) Kinetic Structural Model for the Network Build-Up During the Reaction of Cyanic Acid Esters with Glycidyl Ethers, Journal of Macromolecular Science: Part A-Chemistry, 27: 1, 97-116" and "Shimp, DA, HF, Ising SJ., Co-reaction of epoxide and cyanate resins, 33rd Int SAMPE Symp 1988, 33, 754-766", the teachings of which are incorporated herein by reference. Cyanates can be co-cured or blended with other types of monomers (e.g., epoxides, phenols, imides, alkenes, and acrylates) to form interpenetrating networks (IPNs) or semi-IPNs, thereby further improving film properties and cure kinetics.
[0053] According to another embodiment, cyanate esters can be co-blended with bismaleimide (BMI). Such blends can combine the excellent mechanical properties of cyanate esters and the excellent heat resistance of BMI. In addition to BMI, derivatives of BMI can also be used as blending components for cyanate ester modification and improving its performance.
[0054] In one embodiment, coating 120 can be applied as an uncured coating precursor mixture and then cured. "Coating precursor mixture" refers to a liquid solution of cyanate or other precursors in a cured polycyanurate material applied to glass body 102. In some embodiments, the coating precursor mixture should include one or more organic solvents and polymer precursors (e.g., cyanate). The coating precursor mixture can include one or more chemical components containing a certain material, which will become a component in coating 120 after the coated glass container 100 is applied and cured (e.g., by spraying or dipping, followed by heating). That is, at least some atoms in the precursor will become atoms in the formed coating. In other embodiments, prepolymers or even fully polymerized polycyanurates can be included in the coating precursor mixture.
[0055] Reference again Figure 1 and 2 , if the coating 120 comprises a single layer, the coating 120 can be applied in a single deposition step. The deposition can be performed by an immersion process, or alternatively, the coating 120 can be applied by spraying or other suitable means and optionally dried. A description of suitable deposition methods for the coating 120 described herein can be found in U.S. Patent Application No. 13 / 780,740, entitled "Glass Articles with Low-Friction Coatings", which is incorporated herein by reference in its entirety. In other embodiments, multiple depositions can be used. For example, multiple depositions of the coating precursor mixture can be performed and then cured, or each deposition step can be cured to apply a second coating of the precursor to the cured layer. It should be understood that the deposition technique can depend on the geometry of the glass article.
[0056] After the coating precursor mixture is deposited, at least a portion of the organic solvent of the coating precursor mixture is released by passive drying or by an active drying step (e.g., controlled air flow or high temperature). The coated glass container 100 can then be cured by exposure to heat. As described herein, "curing" refers to any process (usually by heating) that changes the material on the coating from a precursor material to an intermediate or final material. For example, some embodiments use heat curing, which releases the components from the metal oxide precursor and forms a metal oxide. Such curing can include heating the coated vial at a temperature sufficient to polymerize the polycyanurate (e.g., 200° C. to 230° C.). Curing conditions can depend on the type of precursor material used. Without being limited to theory, it is believed that the curing step releases any remaining solvent of the coating precursor mixture.
[0057] The coating 120 applied to the glass body 102 may have a thickness of less than or equal to about 100 μm, less than or equal to about 10 μm, less than or equal to about 8 μm, less than or equal to about 6 μm, less than or equal to about 4 μm, less than or equal to about 3 μm, less than or equal to about 2 μm, or even less than or equal to about 1 μm. In some embodiments, the coating 120 may have a thickness of less than or equal to about 800 nm, less than or equal to about 600 nm, less than or equal to about 400 nm, less than or equal to 300 nm, less than or equal to about 200 nm, or even less than or equal to about 100 nm thick. In other embodiments, the coating 120 may be less than about 90 nm thick, less than about 80 nm thick, less than about 70 nm thick, less than about 60 nm thick, less than about 50 nm thick, or even less than about 25 nm thick. In some embodiments, the thickness of the coating 120 can be at least about 10nm, at least about 15nm, at least about 20nm, at least about 25nm, at least about 30nm, at least about 35nm, at least about 40nm, or even at least about 45nm. Exemplary embodiments can have a thickness of about 20nm to about 50nm, about 25nm to about 45nm, or about 30nm to about 40nm. Without being limited by theory, it is believed that a relatively thin coating (i.e., less than 20nm) may not be enough to protect the glass, thereby causing cracks on the glass surface during the contact between the vials. In addition, such a relatively thin coating may not withstand the depyrogenation process. On the other hand, a relatively thick coating (i.e., greater than 50nm) may be more susceptible to damage and may show wear marks in the coating when the vials are in contact. It should be noted that in the case of a relatively thick coating, it is believed that the wear marks are deformation of the coating rather than deformation of the glass. As described herein, wear marks are visible marks caused by the wear on the coating leaving marks or wear marks. In some embodiments, wear signs may indicate cracking of the glass and / or a relatively high coefficient of friction (eg, 0.7 or greater).
[0058] In some embodiments, the coating 120 may not have a uniform thickness over the entirety of the glass body 102. For example, the coated glass container 100 may have a thicker coating 120 in some areas due to the process of contacting the glass body 102 with one or more coating solutions that form the coating 120. In some embodiments, the coating 120 may have a non-uniform thickness. For example, the coating thickness may vary over different areas of the coated glass container 100, which may help provide protection in selected areas.
[0059] It can be observed that the polycyanurate coating of the present disclosure has several non-limiting advantages over other polymer-based coatings for drug packaging. One such advantage can be a reduced coefficient of friction. For example, a coefficient of friction of less than 0.2, such as about 0.1, has been observed in embodiments of the present disclosure. Additionally or alternatively, due to the stronger physical interaction and chemical reaction between the cyanate ester and the surface silanol of the glass, the cyanate ester can improve the adhesion on the glass surface. In contrast, polyimide coatings may require amino-functionalized alkoxysilanes as coupling agents to enhance coating adhesion, which increases cost and processing difficulty. Additionally or alternatively, cyanate esters, especially F-DCBA, and their prepolymers are easily soluble in various environmentally friendly low-boiling organic solvents, while precursors of other coating systems (e.g., polyimide coatings) may need to be soluble in extremely high boiling solvents, for example, polyamic acid Novastrat 800 is soluble in toluene / DMF, and PMDA-ODA (poly (4,4'-oxydiphenylene tetracarboximide) is soluble in NMP.
[0060] In other embodiments, the cross-linking reaction of cyanate esters for forming polycyanurate can be classified as "click chemistry", which does not produce by-products and does not require additional reagents to promote the formation of cross-linked products-triazine rings. Compared to cross-linking methods based on polycondensation, for example, imide polymerization and silane curing on glass, this can be a significant advantage. In general, polycondensation forms H2O, while silane curing can release MeOH or EtOH. These by-products can be detrimental to the polymerization / curing rate because they push the chemical equilibrium back to the starting material.
[0061] Another advantage may include that the precursors of polycyanurate coatings, cyanate esters and oligomeric tricyanides (e.g., in polycyanurate prepolymers) are readily soluble in commonly used environmentally friendly solvents such as ketones, esters and ethers. In contrast, high temperature thermoplastics, such as PEEK and PPSU, are more difficult to dissolve in solvents at mild temperatures and, therefore, may not be used in solution-based film coating processes.
[0062] In addition or alternatively to other methods disclosed herein, the coating comprising polycyanurate can be substantially transparent for film thicknesses up to 1 micron. This provides a relatively wider processing window if transparency is desired.
[0063] In other embodiments, the coating 120 comprising polycyanurate disclosed herein can be an amorphous material due to the triazine ring functionality formed during the thermal curing process. This can provide the coating 120 with excellent anisotropic properties in physical and chemical properties, as well as excellent dimensional stability after curing.
[0064] The glass container of the pharmaceutical packaging to which the coating 120 may be applied may be formed from a variety of different glass compositions. The specific composition of the glass article may be selected according to the specific application so that the glass has a desired set of physical properties. According to one or more embodiments, the glass may be a composition known to exhibit chemical durability and low thermal expansion, such as an alkali borosilicate glass. According to another embodiment, the glass container may be formed from Type I B glass according to ASTM Standard E438-92.
[0065] The glass container can be made of a glass with a coefficient of thermal expansion of about 25x10 -7 / ℃ to 80x10 -7 / °C range. For example, in some embodiments described herein, the glass body 102 is formed of an alkali aluminosilicate glass composition that withstands ion exchange strengthening. Such a composition generally comprises a combination of SiO2, Al2O3, at least one alkaline earth metal oxide, and one or more alkali metal oxides (such as Na2O and / or K2O). In some of these embodiments, the glass composition may be free of boron and compounds comprising boron. In some other embodiments, the glass composition may also contain a small amount of one or more additional oxides, such as SnO2, ZrO2, ZnO, TiO2, As2O3, etc. These components may be added as clarifiers and / or these components may be added to further enhance the chemical durability of the glass composition. In another embodiment, the glass surface may include a metal oxide coating containing SnO2, ZrO2, ZnO, TiO2, As2O3, etc.
[0066] In some embodiments described herein, the glass body 102 is strengthened, for example by ion exchange strengthening, which is referred to herein as "ion exchanged glass". For example, the compressive stress of the glass body 102 can be greater than or equal to about 300 MPa, or even greater than or equal to about 350 MPa. In some embodiments, the compressive stress can be in the range of about 300 MPa to about 900 MPa. However, it should be understood that in some embodiments, the compressive stress in the glass can be less than 300 MPa or greater than 900 MPa. In some embodiments, the depth of layer of the glass body 102 can be greater than or equal to 20 μm. In some of these embodiments, the depth of layer can be greater than 50 μm or even greater than or equal to 75 μm. In other embodiments, the depth of layer can be as large as or greater than 100 μm. Ion exchange strengthening can be performed in a molten salt bath maintained at a temperature of about 350° C. to about 500° C. In order to obtain the desired compressive stress, the glass container (uncoated) can be immersed in the salt bath for less than about 30 hours or even less than about 20 hours. For example, in one embodiment, a glass container is immersed in a 100% KNO3 salt bath at 450°C for about 8 hours.
[0067] In one specific exemplary embodiment, the glass body 102 can be formed from an ion-exchangeable glass composition described in pending U.S. patent application Ser. No. 13 / 660,894, filed on Oct. 25, 2012, and entitled “Glass Compositions with Improved Chemical and Mechanical Durability,” assigned to Corning, Incorporated.
[0068] However, it should be understood that the coated glass container 100 described herein can be formed from other glass compositions, including but not limited to ion-exchangeable glass compositions and non-ion-exchangeable glass compositions. For example, in some embodiments, the glass container can be formed from a Type 1B glass composition, such as a Type 1B borosilicate glass from Schott.
[0069] In some embodiments described herein, the glass article can be formed of a glass composition that meets the pharmaceutical glass standards described by regulatory agencies based on the hydrolysis resistance of pharmaceutical glasses, such as USP (United States Pharmacopoeia), EP (European Pharmacopoeia), and JP (Japanese Pharmacopoeia). According to USP 660 and EP 7, borosilicate glass meets the Type I standard and is routinely used for parenteral packaging. Examples of borosilicate glass include, but are not limited to 7740, 7800 and Wheaton 180, 200 and 400, Schott Duran, Schott Fiolax, N-51A, Gerrescheimer GX-51 Flint, and others. Soda lime glass meets the Type III standard and is acceptable in packaging dry powders that are subsequently dissolved to form solutions or buffers. Type III glass is also suitable for packaging liquid formulations that are proven to be insensitive to alkalis. Examples of Type III soda lime glass include Wheaton 800 and 900. Dealkalized soda lime glass has higher levels of sodium hydroxide and calcium oxide and meets the Type II standard. These glasses are less resistant to leaching than Type I glasses, but more resistant than Type III glasses. Type II glass can be used for products that maintain a pH below 7 during shelf life. Examples include soda lime glass treated with ammonium sulfate. These pharmaceutical glasses have different chemical compositions and have a linear thermal expansion coefficient (CTE) ranging from 20-85x 10 -7 / ℃ range.
[0070] When the coated glass article described herein is a glass container, the glass body 102 of the coated glass container 100 can take a variety of different forms. For example, the glass body described herein can be used to form a coated glass container 100, such as a vial, an ampoule, a cartridge, a syringe body, and / or any other glass container for storing a pharmaceutical composition. In addition, the ability to chemically strengthen the glass container before coating can be used to further improve the mechanical durability of the glass container. Therefore, it should be understood that in at least one embodiment, the glass container can be ion exchange strengthened before applying the coating. Alternatively, other strengthening methods, such as heat tempering, flame polishing, and lamination described in U.S. Pat. No. 7,201,965 can be used to strengthen the glass before coating.
[0071] Various properties (i.e., coefficient of friction, horizontal compressive strength, four-point bending strength) of the coated glass containers can be measured when the coated glass containers are in the as-coated condition (i.e., after the coating is applied and without any additional treatment other than curing (if applicable)) or after undergoing one or more processing treatments, such as similar or the same treatments performed on a pharmaceutical filling line, including but not limited to washing, lyophilization, depyrogenation, autoclaving, etc.
[0072] Depyrogenation is the process of removing pyrogens from a substance. Depyrogenation of glass products (such as pharmaceutical packaging) can be carried out by applying heat treatment to the sample, wherein the sample is heated to a high temperature and lasts for a period of time. For example, depyrogenation can include heating the glass container to a temperature of about 250°C to about 380°C for a period of about 30 seconds to about 72 hours, including but not limited to 20 minutes, 30 minutes, 40 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours, 24 hours, 48 hours and 72 hours. After heat treatment, the glass container is cooled to room temperature. A conventional depyrogenation condition commonly used in the pharmaceutical industry is heat treatment for about 30 minutes at a temperature of about 250°C. However, it is expected that the time of heat treatment can be shortened if a higher temperature is used. The coated glass container described herein can be exposed to high temperature for a period of time. The high temperature and heated period described herein may be sufficient or may not be sufficient to remove pyrogens from the glass container. However, it should be understood that some heating temperatures and times described herein are sufficient to remove pyrogens from coated glass containers such as coated glass containers described herein. For example, as described herein, the coated glass container can be exposed to a temperature of about 250° C., about 260° C., about 270° C., about 280° C., about 290° C., about 300° C., about 310° C., about 320° C., about 330° C., about 340° C., about 350° C., about 360° C., about 370° C., about 380° C., about 390° C., or about 400° C. for a period of 30 minutes. It should be recognized that the depyrogenation process can be performed for other times than 30 minutes, and 30 minutes and depyrogenation temperatures are used throughout this disclosure for comparative purposes, such as coefficient of friction testing performed after exposure to defined depyrogenation conditions.
[0073] As used herein, lyophilized conditions (i.e., freeze drying) refer to a process in which a sample is filled with a liquid containing protein and then frozen at a low temperature (e.g., -100°C) followed by water sublimation under vacuum at a certain temperature (e.g., -15°C) for a period of time (e.g., 20 hours).
[0074] As used herein, autoclave conditions refer to steam purging the sample at 100°C for a period of time (eg, 10 minutes), followed by a 20 minute dwell period exposing the sample to a 121°C environment, followed by a 30 minute heat treatment at 121°C.
[0075] The coefficient of friction (μ) of the portion of the coated glass container having the coating can be lower than the coefficient of friction of the surface of the uncoated glass container formed by the same glass composition. The coefficient of friction (μ) is a quantitative measurement of the friction between two surfaces and varies according to the mechanical and chemical properties of the first surface and the second surface, including surface roughness and environmental conditions, such as, but not limited to, temperature and humidity. As used herein, the coefficient of friction measurement of the coated glass container 100 is reported as the coefficient of friction between the outer surface of the first glass container (with an outer diameter between about 16.00 mm and about 17.00 mm) and the outer surface of the second glass container, which is substantially the same as the first glass container, wherein the first glass container and the second glass container have the same body and the same coating composition (when applied) and are exposed to the same environment before, during and after manufacturing. Unless otherwise indicated herein, the coefficient of friction refers to the maximum coefficient of friction measured with a normal load of 30N measured on a vial-on-vial test bench as described herein. However, it should be understood that a coated glass container that exhibits a maximum coefficient of friction under a specific applied load will also exhibit the same or better (i.e., lower) maximum coefficient of friction under a smaller load. For example, if a coated glass container exhibits a maximum coefficient of friction of 0.5 or less under an applied load of 50 N, then a coated glass container will also exhibit a maximum coefficient of friction of 0.5 or less under an applied load of 25 N. For measuring the maximum coefficient of friction, local maxima at or near the beginning of the test are excluded, because such maxima at or near the beginning of the test represent the static coefficient of friction. As described in the embodiments herein, the coefficient of friction is measured when the speed of the containers relative to each other is about 0.67 mm / s.
[0076] In the embodiments described herein, the coefficient of friction of glass containers (coated and uncoated) was measured using a vial-on-vial test rig. Figure 3The test bench 200 is schematically shown. The same device can also be used to measure the friction between two glass containers located in the bench. The vial-on-vial test bench 200 includes a first fixture 212 and a second fixture 222 arranged in a cross configuration (i.e., perpendicular to each other). The first fixture 212 includes a first fixed arm 214 attached to a first base 216. The first fixed arm 214 is attached to the first glass container 210 and keeps the first glass container 210 stationary relative to the first fixture 212. Similarly, the second fixture 222 includes a second fixed arm 224 attached to a second base 226. The second fixed arm 224 is attached to the second glass container 220 and keeps it stationary relative to the second fixture 222. The first glass container 210 is located on the first fixture 212 and the second glass container 220 is located on the second fixture 222, so that the longitudinal axis of the first glass container 210 and the longitudinal axis of the second glass container 220 are at an angle of about 90° relative to each other and are located on a horizontal plane defined by the xy axis.
[0077] The first glass container 210 is positioned to contact the second glass container 220 at the contact point 230. A normal force is applied in a direction perpendicular to the horizontal plane defined by the xy axis. The normal force can be applied by a static weight or other force applied to the second fixture 222, which is located on the stationary first fixture 212. For example, a weight can be located on the second substrate 226 and the first substrate 216 can be placed on a stable surface to generate a measurable force between the first glass container 210 and the second glass container 220 at the contact point 230. Alternatively, the force can be applied by a mechanical device, such as a UMT (Universal Mechanical Tester) machine.
[0078] Either the first fixture 212 or the second fixture 222 can be moved relative to the other in a direction that is 45° to the longitudinal axis of the first glass container 210 and the second glass container 220. For example, the first fixture 212 can be kept stationary and the second fixture 222 can be moved so that the second glass container 220 moves across the first glass container 210 in the direction of the x-axis. A similar device is described in Scratch Resistant Polyimide Coatings for Alumino Silicate Glass surfaces by RL De Rosa et al., The Journal of Adhesion, 78: 113-127, 2002. To measure the coefficient of friction, the force required to move the second fixture 222 and the normal force applied to the first glass container 210 and the second glass container 220 are measured with a load cell, and the coefficient of friction is calculated as the quotient of the friction force and the normal force. The stage is operated in an environment of 25° C. and 50% relative humidity.
[0079] In the embodiments described herein, the portion of the coated glass container having the coating has a coefficient of friction of less than or equal to about 0.7 relative to a similar coated glass container, as determined using the above-described vial-on-vialet table. In other embodiments, the coefficient of friction may be less than or equal to about 0.6, or even less than or equal to about 0.5. In some embodiments, the portion of the coated glass container having the coating has a coefficient of friction of less than or equal to about 0.4, or even less than or equal to about 0.3. Coated glass containers having a coefficient of friction of less than or equal to about 0.7 generally exhibit enhanced resistance to friction damage and therefore have improved mechanical properties. For example, the coefficient of friction of a conventional glass container (without a coating) may be greater than 0.7.
[0080] In some embodiments described herein, the coefficient of friction of the portion of the coated glass container having the coating is at least 20% less than the coefficient of friction of the surface of the uncoated glass container formed from the same glass composition. For example, the coefficient of friction of the portion of the coated glass container having the coating can be at least 20% less, at least 25% less, at least 30% less, at least 40% less, or even at least 50% less than the coefficient of friction of the surface of the uncoated glass container formed from the same glass composition.
[0081] In some embodiments, after exposing the coated portion of the coated glass container to a temperature of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C for a period of 30 minutes, the coefficient of friction may be less than or equal to about 0.7. In other embodiments, the coefficient of friction of the coated glass container may be less than or equal to about 0.7 (i.e., less than or equal to about 0.6, less than or equal to about 0.5, less than or equal to about 0.4, or even less than or equal to about 0.3) after exposing the coated portion of the coated glass container to a temperature of about 250° C., about 260° C., about 270° C., about 280° C., about 290° C., about 300° C., about 310° C., about 320° C., about 330° C., about 340° C., about 350° C., about 360° C., about 370° C., about 380° C., about 390° C., or about 400° C. for a period of 30 minutes. In some embodiments, the coefficient of friction of the coated glass container may increase by no more than about 30% after exposing the coated portion of the coated glass container to a temperature of about 250° C. (or about 260° C.) for 30 minutes. In other embodiments, the coefficient of friction of the coated glass container may increase by no more than about 30% (i.e., about 25%, about 20%, about 15%, or even about 10%) after exposing the coated portion of the coated glass container to a temperature of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C for a period of 30 minutes. In other embodiments, after exposing the coated portion of the coated glass container to a temperature of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C for a period of 30 minutes, its coefficient of friction may increase by no more than about 0.5 (i.e., about 0.45, about 0.4, about 0.35, about 0.3, about 0.25, about 0.2, about 0.15, about 0.1, or even about 0.05). In some embodiments, the coefficient of friction of the coated glass container may not increase at all after exposing the coated portion of the glass container to a temperature of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C for a period of 30 minutes.
[0082] In some embodiments, the coefficient of friction of the portion of the coated glass container having the coating may be less than or equal to about 0.7 after immersion in a water bath at a temperature of about 70° C. for 10 minutes. In other embodiments, the coefficient of friction of the portion of the coated glass container having the coating may be less than or equal to about 0.7 (i.e., less than or equal to about 0.6, less than or equal to about 0.5, less than or equal to about 0.4, or even less than or equal to about 0.3) after immersion in a water bath at a temperature of about 70° C. for 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or even 1 hour. In some embodiments, the coefficient of friction of the portion of the coated glass container having the coating may increase by no more than about 30% after immersion in a water bath at a temperature of about 70° C. for 10 minutes. In other embodiments, the coefficient of friction of the coated portion of the coated glass container may increase by no more than about 30% (i.e., about 25%, about 20%, about 15%, or even about 10%) after being immersed in a water bath at a temperature of about 70° C. for 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or even 1 hour. In some embodiments, the coefficient of friction of the coated portion of the coated glass container may not increase at all after being immersed in a water bath at a temperature of about 70° C. for 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or even 1 hour.
[0083] In some embodiments, after exposure to freeze-drying conditions, the coefficient of friction of the portion of the coated glass container with the coating may be less than or equal to about 0.7. In other embodiments, after exposure to freeze-drying conditions, the coefficient of friction of the portion of the coated glass container with the coating may be less than or equal to about 0.7 (i.e., less than or equal to about 0.6, less than or equal to about 0.5, less than or equal to about 0.4, or even less than or equal to about 0.3). In some embodiments, after exposure to freeze-drying conditions, the coefficient of friction of the portion of the coated glass container with the coating may increase by no more than about 30%. In other embodiments, after exposure to freeze-drying conditions, the coefficient of friction of the portion of the coated glass container with the coating may increase by no more than about 30% (i.e., about 25%, about 20%, about 15%, or even about 10%). In some embodiments, after exposure to freeze-drying conditions, the coefficient of friction of the portion of the coated glass container with the coating may not increase at all.
[0084] In some embodiments, after exposure to autoclave conditions, the coefficient of friction of the coated portion of the glass container may be less than or equal to about 0.7. In other embodiments, after exposure to autoclave conditions, the coefficient of friction of the coated portion of the glass container may be less than or equal to about 0.7 (i.e., less than or equal to about 0.6, less than or equal to about 0.5, less than or equal to about 0.4, or even less than or equal to about 0.3). In some embodiments, after exposure to autoclave conditions, the coefficient of friction of the coated portion of the glass container may increase by no more than about 30%. In other embodiments, after exposure to autoclave conditions, the coefficient of friction of the coated portion of the glass container may increase by no more than about 30% (i.e., about 25%, about 20%, about 15%, or even about 10%). In some embodiments, after exposure to autoclave conditions, the coefficient of friction of the coated portion of the glass container may not increase at all.
[0085] The coated glass container described herein has horizontal compressive strength. As described herein, horizontal compressive strength is measured by the following: the coated glass container 100 is placed horizontally between two parallel press plates oriented parallel to the longitudinal axis of the glass container. Then, in the direction perpendicular to the long axis of the glass container, a mechanical load is applied to the coated glass container 100 using a press plate. Before being placed in the press plate, the glass container is wrapped in 2 inches of tape, and the protruding part is cut off or folded around the bottom of the container. The container is then placed in an index card nailed around the sample. The load rate of the vial compression is 0.5 inches / minute, which means that the press plates move toward each other at a rate of 0.5 inches / minute. The horizontal compressive strength is measured at 25°C ± 2°C and 50% ± 5% relative humidity. In some embodiments, it is expected that a horizontal compression test is performed within 1 hour (and no more than 24 hours) after removing the pyrogen to simulate the conditions of the drug filling line. The horizontal compressive strength is a load measurement at failure, and the measured value of the horizontal compressive strength can be given as the probability of failure under the selected normal compression load. As used herein, failure occurs when the glass container breaks under horizontal compression in at least 50% of the samples. Thus, horizontal compression is provided to a set of samples. In some embodiments, the horizontal compression strength of the coated glass container may be at least 10%, 20%, or 30% greater than that of an uncoated vial.
[0086] Reference now Figure 1 and 3, horizontal compression strength measurements can also be performed on worn glass containers. Specifically, the operation of the test bench 200 may cause damage to the coated glass container outer surface 122, such as surface scratches or wear, which weakens the strength of the coated glass container 100. The glass container is then subjected to the above-mentioned horizontal compression procedure, in which the container is placed between two pressing plates and the scratches are parallel to the pressing plates and point outward. The scratches can be characterized by the selected normal pressure and scratch length applied by the vial-on-vialet table. Unless otherwise stated, the scratches of the worn glass containers in the horizontal compression procedure are characterized by a scratch length of 20 mm generated by a normal load of 30 N. It is desirable that the scratches can be angled at 90o ± 5 ° relative to the pressing plates.
[0087] The horizontal compressive strength of the coated glass container can be evaluated after heat treatment. The heat treatment can be exposure to a temperature of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or 400°C for a period of 30 minutes. In some embodiments, after the coated glass container is exposed to a heat treatment (such as the heat treatment described above) and then subjected to the above-described abrasion, its horizontal compressive strength decreases by no more than about 20%, 30%, or even 40%. In one embodiment, the horizontal compressive strength of the coated glass container decreases by no more than about 20% after exposure to a heat treatment at a temperature of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C or about 400°C for a period of 30 minutes and then abrasion.
[0088] The coated glass articles described herein may be thermally stable after being heated to a temperature of at least 250° C. (or 260° C., or 280° C., or 300° C.) for a period of 30 minutes. The term "thermally stable" as used herein means that after exposure to high temperature, the coating applied to the glass article remains substantially intact on the surface of the glass article, such that after exposure, the mechanical properties of the coated glass article, specifically the coefficient of friction and horizontal compressive strength, are minimally affected, if at all. This indicates that after high temperature exposure, the coating remains adhered to the glass surface and continues to protect the glass article from mechanical damage, such as abrasion, impact, etc.
[0089] In the embodiments described herein, a coated glass article is considered thermally stable if it meets the coefficient of friction criterion and the horizontal compressive strength criterion after being heated to a specified temperature and maintained at that temperature for a specified time. To determine whether the coefficient of friction criterion is met, use Figure 3 The coefficient of friction of the first coated glass article in the as received condition (i.e., before any thermal exposure) was determined using the test stand shown and an applied load of 30 N. The second coated glass article (i.e., a glass article having the same glass composition and the same coating composition as the first coated glass article) was thermally exposed to the specified conditions and cooled to room temperature. Subsequently, the coefficient of friction of the first coated glass article was determined using the test stand shown and an applied load of 30 N. Figure 3 The coefficient of friction of the second glass article is determined by a test bench as shown, and the coated glass article is abraded with an applied load of 30 N to obtain a wear (i.e., a "scratch") of approximately 20 mm in length. If the coefficient of friction of the second coated glass article is less than 0.7 and the glass surface of the second glass article does not have any observable damage in the abraded area, the friction coefficient criteria for determining the thermal stability of the coating are met. As used herein, the term "observable damage" means that when viewed with a Nomarski or differential interference contrast (DIC) spectroscopic microscope with an LED or halogen light source at 100 times magnification, the glass surface in the abraded area of the glass article contains less than six glass cracks per 0.5 cm of the length of the abraded area. The standard definition of glass cracks or glass cracking is described in "NIST Recommended Practice Guide: Fractography of Ceramics and Glasses" by GD Quinn, NIST Special Publication 960-17 (2006).
[0090] To determine compliance with the horizontal compressive strength standard, the Figure 3 The first coated glass article was abraded in the test stand shown to form a 20 mm scratch. The first coated glass article was then subjected to a horizontal compression test as described herein, and the residual strength of the first coated glass article was determined. The second coated glass article (i.e., a glass article having the same glass composition and the same coating composition as the first coated glass article) was thermally exposed to the specified conditions and cooled to room temperature. Subsequently, under a load of 30 N, the first coated glass article was subjected to a horizontal compression test as described herein, and the residual strength of the first coated glass article was determined. Figure 3The second coated glass article is abraded in the test rig shown. The second coated glass article is then subjected to horizontal compression testing as described herein, and the residual strength of the second coated glass article is determined. If the residual strength of the second coated glass article does not decrease by more than about 20% relative to the first coated glass article (i.e., the failure load does not decrease by more than 20%), the horizontal compressive strength criteria for determining the thermal stability of the coating are met.
[0091] If the coated glass container meets the coefficient of friction standard and the horizontal compressive strength standard after being exposed to a temperature of at least about 250°C (or 260°C or 280°C) for a period of at least about 30 minutes, the coated glass container is considered to be thermally stable [i.e., the coated glass container is thermally stable at a temperature of at least about 250°C (or 260°C or 280°C) for a period of about 30 minutes]. Thermal stability can also be evaluated at temperatures of about 250°C (or 260°C or 280°C) up to about 400°C. For example, in some embodiments, the coated glass container is considered to be thermally stable if it meets the standard at a temperature of at least about 270°C or even about 280°C for a period of about 30 minutes. In other embodiments, the coated glass container is considered to be thermally stable if it meets the standard at a temperature of at least about 290°C or even about 300°C for a period of about 30 minutes. In other embodiments, the coated glass container is considered thermally stable if it meets the standard for a period of about 30 minutes at a temperature of at least about 310°C or even about 320°C. In other embodiments, the coated glass container is considered thermally stable if it meets the standard for a period of about 30 minutes at a temperature of at least about 330°C or even about 340°C. In other embodiments, the coated glass container is considered thermally stable if it meets the standard for a period of about 30 minutes at a temperature of at least about 350°C or even about 360°C. In other embodiments, the coated glass container is considered thermally stable if it meets the standard for a period of about 30 minutes at a temperature of at least about 370°C or even about 380°C. In other embodiments, the coated glass container is considered thermally stable if it meets the standard for a period of about 30 minutes at a temperature of at least about 390°C or even about 400°C.
[0092] The coated glass containers disclosed herein may also be thermally stable over a range of temperatures, meaning that at each temperature in the range, the coated glass containers are thermally stable in terms of meeting the coefficient of friction criteria and the horizontal compressive strength criteria. For example, in the embodiments described herein, the coated glass containers may be thermally stable from at least about 250°C (or 260°C or 280°C) to a temperature of less than or equal to about 400°C. In some embodiments, the coated glass containers may be thermally stable from at least about 250°C (or 260°C or 280°C) to about 350°C. In some other embodiments, the coated glass containers may be thermally stable from at least about 280°C to a temperature of less than or equal to about 350°C. In other embodiments, the coated glass containers may be thermally stable from at least about 290°C to about 340°C. In another embodiment, the coated glass containers may be thermally stable over a temperature range of about 300°C to about 380°C. In another embodiment, the coated glass containers may be thermally stable over a temperature range of about 320°C to about 360°C.
[0093] The coated glass containers described herein have a four-point bending strength. To measure the four-point bending strength of the glass container, a glass tube was used for measurement, which was a precursor to the coated glass container 100. The diameter of the glass tube was the same as that of the glass container, but did not include a glass container base or a glass container mouth (i.e., before the glass tube was formed into a glass container). The glass tube was then subjected to a four-point bending stress test to induce mechanical failure. The test was conducted at 50% relative humidity, with each external contact element spaced 9" apart and each internal contact element spaced 3" apart at a load application rate of 10 mm / min.
[0094] Four-point bending stress measurements may also be performed on the coated and abraded tubes. Operating the test station 200 may produce abrasions on the tube surface, such as surface scratches, which weaken the tube as described in measuring the horizontal compressive strength of abraded vials. The glass tubes are then subjected to a four-point bending stress test to induce mechanical failure. The test is conducted at 25°C and 50% relative humidity, at a load application rate of 10 mm / min, using external probes spaced 9" apart, and each internal contact element spaced 3", while positioning the tube so that the scratches are in tension during the test.
[0095] In some embodiments, the coated glass tube exhibits a four-point bending strength after abrasion that is, on average, at least 10%, 20%, or even 50% higher than the mechanical strength of an uncoated glass tube abraded under the same conditions.
[0096] In some embodiments, after the coated glass container 100 is worn by the same glass container at a normal force of 30 N, the coefficient of friction of the worn area of the coated glass container 100 increases by no more than about 20% after another wear by the same glass container at the same location at a normal force of 30 N, or does not increase at all. In other embodiments, after the coated glass container 100 is worn by the same glass container at a normal force of 30 N, the coefficient of friction of the worn area of the coated glass container 100 increases by no more than about 15% or even 10% after another wear by the same glass container at the same location at a normal force of 30 N, or does not increase at all. However, not all embodiments of the coated glass container 100 need to exhibit this property.
[0097] The transparency and color of the coated container can be evaluated by measuring the transmittance of the container in the wavelength range between 400-700nm using a spectrophotometer. The measurement is performed as follows: the light beam is directed perpendicular to the container wall so that the light beam passes through the coating twice-the first time when entering the container and then when leaving the container. In some embodiments, for wavelengths of about 400nm to about 700nm, the transmittance through the coated glass container can be greater than or equal to about 55% of the transmittance through the uncoated glass container (through the two walls of the container). As described herein, the transmittance can be measured before or after heat treatment, such as the heat treatment described herein. For example, for each wavelength of about 400nm to about 700nm, the transmittance can be greater than or equal to about 55% of the transmittance through the uncoated glass container. In other embodiments, for wavelengths of about 400 nm to about 700 nm, the transmittance of light through the coated glass container is greater than or equal to about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, or even about 90% of the transmittance of light through the uncoated glass container.
[0098] As described herein, the transmittance can be measured before or after an environmental treatment (e.g., a heat treatment as described herein). For example, after a heat treatment period of 30 minutes at about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C, or after exposure to lyophilization conditions, or after exposure to autoclave conditions, for wavelengths from about 400 nm to about 700 nm, the transmittance through the coated glass container is greater than or equal to about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, or even about 90% of the transmittance through the uncoated glass container.
[0099] Yellowing caused by exposure to heat treatment can be measured by x and y coordinates according to the CEI 1931 color space and discussed with the examples provided herein. The change in x and y coordinates after removal of the pyrogenic conditions can demonstrate yellowing of the coated glass article.
[0100] In some embodiments, the coated glass container 100 can be considered colorless and transparent to the naked human eye when viewed at any angle. In other embodiments, the coating 120 can have a perceptible color when, for example, the coating 120 includes a colored polymer.
[0101] In some embodiments, the coated glass container 100 can have a coating 120 capable of receiving an adhesive label. That is, the coated glass container 100 can receive an adhesive label on the coated surface so that the adhesive label is securely attached. However, the ability to attach an adhesive label is not a requirement for all embodiments of the coated glass container 100 described herein.
[0102] Example
[0103] Various embodiments of the glass container with coating are further described by the following examples. These examples are illustrative in nature and should not be construed as limiting the subject matter of the present disclosure. In the examples, all reported CoF data are average CoFs, rather than the maximum CoFs described herein.
[0104] Example 1
[0105] The cyanate monomers were compared to estimate their solubility in various commonly used commercial solvents. The selected monomers were bisphenol A cyanate (DCBA), C,C'-[(dimethylsilylene)di-4,1-phenylene] ester (Si-DCBA) and C,C'-((2,2,2-trifluoro-1-(trifluoromethyl)ethylidene)di-4,1-phenylene) ester (F-DCBA). The selected solvents were ethanol, methanol, acetone, butanone (also known as methyl ethyl ketone (MEK)), dichloromethane (CH2Cl2), propylene glycol methyl ether acetate (PGMEA) and acetonitrile. Sample solutions were prepared by dissolving 50 mg of cyanate monomer powder in 10 mL of solvent. Sample solutions of each monomer in each solvent were prepared. The sample solutions were observed to determine the time taken before the monomer became completely dissolved, that is, the time taken before the sample solution became completely transparent. Monomers in sample solutions that took more than 30 minutes to become completely transparent were considered to be incompletely soluble. The results are recorded in Table 1 below.
[0106] Table 1
[0107]
[0108]
[0109] As shown in Table 1, DCBA can be completely dissolved in CH2Cl2, PGMEA, acetone, MEK and acetonitrile within a few seconds to a few minutes, but is not completely soluble in ethanol or methanol. F-DCBA shows excellent solubility and can be completely dissolved in all solvents within a few seconds. Si-DCBA shows the worst solubility and cannot be completely dissolved in any solvent. Si-DCBA shows particularly low transparency in ethanol and methanol solutions.
[0110] Example 2
[0111] The percent transmission of two groups of coated glass wafers was tested to evaluate the transparency of various cyanate ester coatings in the UV-visible range. The first group (glass 1-5) was 1 mm thick and the second group (glass 6-10) was 2 mm thick. The percent transmission of glasses 1 and 7 was tested in an uncoated condition. The percent transmission of glass 2 was tested after spin coating with F-DCBA prepolymer coating. The percent transmission of glasses 3-6 was tested after spin coating with 30 mg / mL, 20 mg / mL, 10 mg / mL and 5 mg / mL F-DCBA monomer coatings, respectively. The percent transmission of glass 8 was tested after spin coating with DCBA prepolymer coating. The percent transmission of glasses 9-10 was tested after spin coating with 30 mg / mL and 20 mg / mL DCBA monomer coatings, respectively. The results are shown in Figure 1. Figure 4 and recorded in Table 2 below. Figure 4 , line 301 represents data for glasses 1-5, and line 302 represents data for glasses 6-10.
[0112] Table 2
[0113] serial number coating Glass thickness transmission% Glass 1 Uncoated 1mm 92.08 Glass 2 F-DCBA prepolymer solution 1mm 91.77 Glass 3 30mg / mL F-DCBA monomer solution 1mm 92.06 Glass 4 20mg / mL F-DCBA monomer solution 1mm 92.06 Glass 5 10mg / mL F-DCBA monomer solution 1mm 91.88 Glass 6 5mg / mL F-DCBA monomer solution 1mm 92.06 Glass 7 Uncoated 2mm 91.88 Glass 8 DCBA prepolymer solution 2mm 91.77 Glass 9 30mg / mL DCBA monomer solution 2mm 91.41 Glass 10 20mg / mL DCBA monomer solution 2mm 92.00
[0114] As shown in Table 2, the thickness of the glass wafer, the cyanate ester, the coating solution concentration, and whether the coating solution was reflowed to form the prepolymer solution had little effect on the final optical properties of the glass. When comparing the uncoated glass wafer to the coated glass wafer, the percent transmission decreased by no more than 0.5%. In addition, the reference Figure 4 , any difference between the percent transmission of the two sets of coated vials is almost entirely within the UV range (10-400 nm). That is, any effect of these properties on the percent transmission will not be detectable by visual inspection.
[0115] Example 3
[0116] The pharmaceutical packaging vials were dip coated in the F-DCBA monomer coating, and the coating was subsequently cured (initial cure). After curing, the CoF of the coated vials was tested by the test procedure as described herein. The coated vials were then subjected to a further heat treatment (second heat treatment) of 30 minutes at 260°C, and the CoF was tested again. Finally, the coated vials were subjected to another heat treatment (final heat treatment) of 16 hours at 335°C, and the CoF was tested. The results are recorded in Table 3 below.
[0117] Table 3
[0118] Force (N) Location Average CoF 5 After initial curing 0.100 5 After the second heat treatment 0.431 5 After final heat treatment 0.923 30 After initial curing 0.128 30 After the second heat treatment 0.406 30 After final heat treatment 0.762
[0119] As shown in Table 3, after the initial curing process, the coated vials have excellent CoF values. However, after the heat treatment, the CoF values increase significantly. This increase in CoF values may be due to the coating not being fully cured, indicating that temperatures above 200°C may be required to achieve complete crosslinking and excellent heat resistance. In addition, this increase in CoF values may be due to the decomposition of F-DCBA caused by side reactions during the coating and curing process. Compared to DCBA, F-DCBA is less stable due to the highly active cyanate ester part, which causes side reactions with both Lewis acids and Lewis bases (such as water and undried solvents). However, the CoF after the second heat treatment is still lower than that of bare glass.
[0120] Example 4
[0121] The contact angle of the F-DCBA monomer coating was tested to characterize the wettability of the liquid on the coating surface. A glass wafer with a size of 50mm x 50mm x 1.1mm was spin-coated with the F-DCBA monomer coating. After spin coating, the F-DCBA monomer was cured at 180°C for 1 hour and cured at 200°C for another 1 hour. After curing, the coated glass wafer was subjected to heating for 16 hours at 335°C. The contact angle was measured by measuring the contact angle between a 2.0 μL water droplet and the surface coated with cyanate. The contact angle was measured immediately after curing, and the contact angle was measured at each stage of the heat resistance test, for a total of six measurements. The results are recorded in Table 4 below.
[0122] Table 4
[0123] Measurement timing Contact Angle After curing 80.1 After 1 hour at 335℃ 79.5 After 2 hours at 335℃ 75.2 After 4 hours at 335℃ 72.0 After 8 hours at 335℃ 70.0 After 16 hours at 335°C 61.5
[0124] As shown in Table 4, the contact angle gradually decreases with the extension of the heating time. This may indicate that the F-DCBA coating gradually decomposes during the heat resistance test. It is believed that this decrease in the contact angle is due to the wettability of the coating surface approaching that of bare glass due to the reduction in coating thickness. Based on the results of Table 4, the contact angle measured after 4 hours at 335°C was selected as the critical heating time for judging the heat resistance of the cyanate ester coating. When compared with the initial state, the change in the contact angle at this time becomes obvious.
[0125] Example 5
[0126] The contact angle and CoF of the DCBA monomer coating were tested in a similar manner as in Example 4. A glass wafer of size 50 mm x 50 mm x 1.1 mm was spin coated with a coating of DCBA monomer in MEK. After spin coating, the DCBA monomer was cured at 180° C. for 1 hour and at 200° C. for an additional hour. After curing, the coated vials were subjected to heating at 335° C. for 8 hours. The contact angle was measured after curing and at various stages of the heat resistance test. The results are recorded in Table 5 below.
[0127] Table 5
[0128] Measurement timing Contact Angle After curing 101.9 After 1 hour at 335℃ 102.4 After 2 hours at 335℃ 98.7 After 4 hours at 335℃ 88.5 After 8 hours at 335℃ 72.9 After 16 hours at 335°C 46.9
[0129] As shown in Table 5, the DCBA coating is more hydrophobic than the F-DCBA coating of Example 4. Although fluorinated compounds such as F-DCBA should have greater hydrophobicity and lubricity, the results show that the DCBA coating can have a contact angle as high as 102.4, compared to the highest contact angle of 80.1 of the F-DCBA coating measured in Example 4. Further, even after 4 hours of heat resistance testing, the DCBA coating has a more excellent contact angle than the initial contact angle of the F-DCBA coating recorded in Table 4. This may be due to the instability of F-DCBA during the curing process, indicating that the F-DCBA coating may tend to decompose faster than the relatively stable DCBA coating.
[0130] Example 6
[0131] Two batches of drug packaging vials were dip coated in DCBA monomer in MEK solvent. The first batch (DCBA-1) was cured at 180°C for 1 hour and cured at 200°C for another 1 hour. The second batch (DCBA-4) was cured at 180°C for 1 hour and cured at 200°C for another 4 hours. After curing, the CoF of the coated vials was tested by the test procedure as described herein. The coated vials were then subjected to further heat treatment for 35 minutes at 320°C and tested for CoF again. Finally, the coated vials were subjected to another heat treatment for 9 hours at 335°C and tested for CoF. The results are recorded in Table 6 below.
[0132] Table 6
[0133] batch force Location Average CoF DCBA-1 5 After initial curing 0.276 DCBA-1 5 After the second heat treatment 0.244 DCBA-1 5 After final heat treatment 0.522 DCBA-1 30 After initial curing 0.263 DCBA-1 30 After the second heat treatment 0.235 DCBA-1 30 After final heat treatment 0.610 DCBA-4 5 After initial curing 0.355 DCBA-4 5 After the second heat treatment 0.330 DCBA-4 5 After final heat treatment - DCBA-4 30 After initial curing 0.295 DCBA-4 30 After the second heat treatment 0.269 DCBA-4 30 After final heat treatment -
[0134] As shown in Table 6, the CoF of DCBA-1 decreases slightly after the second heat treatment, but increases significantly after the extended final heat treatment. Similar to DCBA-1, the CoF of DCBA-4 decreases slightly after the second heat treatment, but the CoF values of DCBA-4 are higher than those of DCBA-1 both after initial curing and after heating. Based on these results, extended curing time may have little effect on the CoF or heat resistance of DCBA coatings.
[0135] Example 7
[0136] The thickness of the DCBA coating applied by spin coating was observed by scanning electron microscopy (SEM). A glass wafer with a size of 50mm x 50mm x1.1mm was spin coated with 20mg / mL DCBA monomer coating and 30mg / mL prepolymer coating. After spin coating, the DCBA coating was cured at 180°C for 1 hour and cured at 200°C for 1 hour. The thickness of the cured coating was then measured using SEM. The average coating thickness of the DCBA monomer coating was 37.7nm. The prepolymer coating was thicker and more viscous, and the average coating thickness was 221nm. Further, a small gap was observed between the prepolymer coating and the glass surface. This can indicate that the viscosity of the coating can be affected by residual solvents during the curing process.
[0137] Example 8
[0138] Observe the thickness of the F-DCBA coating applied by spin coating by SEM.Spin coating a glass wafer with a size of 50mm x 50mm x1.1mm with 20mg / mL F-DCBA monomer coating, 30mg / mL F-DCBA monomer coating and 20mg / mL F-DCBA prepolymer coating.After spin coating, the F-DCBA coating was cured at 180°C for 1 hour, and cured again at 200°C for 1 hour.Then SEM was used to measure the thickness of the cured coating.The average coating thickness of the 20mg / mL F-DCBA monomer coating was 58.2nm.The average coating thickness of the 30mg / mL F-DCBA monomer coating was 158nm.The prepolymer coating was denser and more viscous, and the average coating thickness was 480nm.Further, it was observed that not only the coating thickness increased with the increase of coating concentration, but also the variation of the coating thickness on the glass surface increased.
[0139] It should now be understood that the glass containers with low friction coatings described herein exhibit improved resistance to mechanical damage due to the application of the low friction coating, and thus provide the glass containers with enhanced mechanical durability. This property makes the glass containers very suitable for a variety of applications, including, but not limited to, pharmaceutical packaging materials.
[0140] It is obvious to those skilled in the art that various modifications and changes can be made to the embodiments described herein without departing from the spirit and scope of the subject matter of the patent right. Therefore, this specification is intended to cover the modifications and changes of the various embodiments described herein, as long as these modifications and changes are within the scope of the attached claims and their equivalents.
Claims
1. A drug package, comprising: A glass container, comprising a first surface and a second surface opposite to the first surface, wherein the first surface is an outer surface of the glass container; and a coating disposed over at least a portion of the first surface of the glass container, the coating comprising a polycyanurate, wherein the portion of the first surface of the glass container having the coating has a friction coefficient less than or equal to 0.7, and Wherein, after heat treatment at a temperature of at least 250°C for 30 minutes, the portion of the first surface of the glass container having the coating still maintains a friction coefficient less than or equal to 0.
7.
2. The drug package according to claim 1, wherein: Polycyanurates contain monomer units formed from one or more bisphenol cyanate esters.
3. The drug package according to claim 2, wherein: The one or more bisphenol cyanates are selected from bisphenol A cyanate, bisphenol E cyanate, C,C'-((2,2,2-trifluoro-1-(trifluoromethyl)ethylene)di-4,1-phenylene) ester, tetramethyl bisphenol F cyanate, bisphenol M cyanate, or combinations thereof.
4. The drug package according to claim 1, wherein: The thickness of the coating is 100 nm or less.
5. The drug package according to claim 1, wherein: The coating is in direct contact with at least a portion of the first surface of the glass container.
6. The drug package according to claim 1, wherein: For each wavelength from 400 nm to 700 nm, the transmittance of light through the drug package is greater than or equal to 55% of the transmittance of light through an uncoated drug package.
7. The drug package according to claim 6, wherein: After heat treatment at a temperature of at least 250°C for 30 minutes, the drug package still maintains a light transmittance through the drug package that is greater than or equal to 55% of the light transmittance through the uncoated drug package for each wavelength from 400 nm to 700 nm.
8. A drug package, comprising: A glass container, comprising a first surface and a second surface opposite to the first surface, wherein the first surface is an outer surface of the glass container; and a coating disposed over at least a portion of the first surface of the glass container, the coating being formed from one or more cyanate esters, wherein the portion of the first surface of the glass container having the coating has a friction coefficient less than or equal to 0.7, and Wherein, after heat treatment at a temperature of at least 250°C for 30 minutes, the portion of the first surface of the glass container having the coating still maintains a friction coefficient less than or equal to 0.
7.
9. The drug package according to claim 8, wherein: The one or more cyanate esters are selected from one or more bisphenol cyanate esters.
10. The drug package according to claim 9, wherein: The one or more bisphenol cyanates are selected from bisphenol A cyanate, bisphenol E cyanate, C,C'-((2,2,2-trifluoro-1-(trifluoromethyl)ethylene)di-4,1-phenylene) ester, tetramethyl bisphenol F cyanate, bisphenol M cyanate', or combinations thereof.
11. The drug package according to claim 9, wherein: The thickness of the coating is 100 nm or less.
12. The drug package according to claim 9, wherein: The coating is in direct contact with at least a portion of the first surface of the glass container.
13. The drug package according to claim 9, wherein: For each wavelength from 400 nm to 700 nm, the transmittance of light through the drug package is greater than or equal to 55% of the transmittance of light through an uncoated drug package.
14. A method of producing a coated pharmaceutical package, the method comprising: depositing a precoating mixture onto a first surface of an exterior surface of a glass container, the precoating mixture comprising one or more cyanate esters; as well as heating the coating precursor mixture to form a coating on the outer surface of the glass container, the coating comprising a polycyanurate, wherein the portion of the outer surface of the glass container having the coating has a coefficient of friction less than or equal to 0.7, and Wherein, after heat treatment at a temperature of at least 250°C for 30 minutes, the portion of the outer surface of the glass container having the coating still maintains a friction coefficient less than or equal to 0.
7.
15. The method of claim 14, wherein: The one or more cyanate esters are selected from one or more bisphenol cyanate esters.
16. The method of claim 15, wherein: The one or more bisphenol cyanates are selected from bisphenol A cyanate, bisphenol E cyanate, C,C'-((2,2,2-trifluoro-1-(trifluoromethyl)ethylene)di-4,1-phenylene) ester, tetramethyl bisphenol F cyanate, bisphenol M cyanate', or combinations thereof.
17. The method of claim 15, wherein: The heating of the precoating mixture is carried out at a temperature of less than 230°C.
Citation Information
Patent Citations
Encryption switch processing
US20130066781A1
Glass Articles With Low-Friction Coatings
US20130171456A1
Glass laminate substrate having enhanced impact and static loading resistance
US7201965B2
No title available
GB1305762A
Strengthened borosilicate glass containers with improved damage tolerance
US20140034544A1